2018
DOI: 10.1007/s12325-018-0759-0
|View full text |Cite
|
Sign up to set email alerts
|

A Targeted Literature Review Examining Biologic Therapy Compliance and Persistence in Chronic Inflammatory Diseases to Identify the Associated Unmet Needs, Driving Factors, and Consequences

Abstract: Chronic inflammatory diseases (CIDs) represent a substantial clinical and economic burden to patients, providers, payers and society overall. Biologics, such as tumor necrosis factor inhibitors (TNFi), have emerged as effective treatment options for patients with CIDs. However, the therapeutic potential of biologics is not always achieved in clinical practice, with results from studies examining the use of biologics in real-world settings suggesting lower levels of treatment effectiveness compared with clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 94 publications
0
45
0
Order By: Relevance
“…Increased patient satisfaction has previously been shown to increase patient adherence [23]. Adherence to anti-TNFs for the treatment of CIDs is known to be low (59% [95% confidence interval: 58-60%]) [13], which in turn can reduce disease control and long-term outcomes [10,14]. High patient satisfaction levels with the e-Device may lead to improved adherence and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased patient satisfaction has previously been shown to increase patient adherence [23]. Adherence to anti-TNFs for the treatment of CIDs is known to be low (59% [95% confidence interval: 58-60%]) [13], which in turn can reduce disease control and long-term outcomes [10,14]. High patient satisfaction levels with the e-Device may lead to improved adherence and clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may encounter challenges when self-injecting anti-TNFs [10,11]. These can include patient needle phobia, a lack of confidence in their own ability to safely and effectively administer injections and remembering the dates of their selfinjections [10][11][12]. As a result, adherence to anti-TNF treatment regimens is often suboptimal, negatively impacting patient outcomes and disease control [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The authors did not speculate as to the reasons for sex differences in ECS compliance. Cigarette smoking has been found to be a predictor of noncompliance with prescribed therapy across several fields of research, [8][9][10][11][12][13][14][15][16] and smoking cessation has been reported to be predictive of increased adherence to therapy. 17 To our knowledge, cigarette smoking has not previously been reported as a predictor of noncompliance with compression stocking use.…”
Section: Discussionmentioning
confidence: 99%
“…Self-injection can be beneficial to both patients and caregivers, increasing flexibility and patient independence, reducing caregiver burden and reducing costs for both the patient and the healthcare system [5][6][7][8]. There are a number of barriers to patients successfully and safely selfinjecting anti-TNFs [2,5,6,9]; these include patients' needle phobia, lack of confidence in their ability to self-inject and forgetting to administer medicine [10,11]. These factors can contribute to sub-optimal levels of adherence to anti-TNF drug regimens, which has the potential to negatively impact patient outcomes [12,13].…”
Section: Introductionmentioning
confidence: 99%